Avaliação da patogenicidade e atividade enzimática de fungos entomopatogênicos para o controle de Plutella xylostella (Lepidoptera: Plutellidae) - Bianchini, Flávio Gabriel (2010)
Plutella xylostella, commonly known as diamondback moth, causes great damages in collard greens and broccolis crops of Itabaiana municipality in Sergipe State-BR. Alternative control techniques are being researcher s goals because the intensive use of chemicals has enhancing resistance problems, intoxication of workers, beside the pollution of environment and residues in the products, making difficult their commercialization. Entomogenous fungi have been used widespread in biological control of agriculture pests and have a remarkable role among micro-organisms as an alternative method to control the moth. This work aims to evaluate the pathogenicity of ten isolates of Beauveria and Paecilomyces, from different research institutions, on diamondback moth and also to identify and quantify extra cell enzyme patterns made by the mentioned fungi. The rearing of the moths will be at lab conditions starting from young crawlers and pupae picked up in field crops of collard and broccolis. The enzyme activities will be evaluated in extra cell fluids filtrated from entomogenous fungi reared in aqueous medium. The results obtained from the bioassays will give contribution in the identification of the most efficient genera or isolates to be used in IPM of diamondback moth. Moreover, it is expected that the relationship pathogenicity x enzyme activity be one other tool to characterizing these micro-organisms.